Gambaran Kontaminasi Bakteriologis Udang di Pusat Pasar Tradisional Medan - Yeni Artika; Sartini Sartini; Meida Nugrahalia (Universitas Medan Area, 2021)
Terasi is a culinary concoction made from fermented fish or shrimp. This shrimp paste has a savory taste, but can add flavor to the dish. This study aims to determine the description of bacterial contamination of shrimp paste in traditional markets in the city of Medan. This research was conducted descriptively by describing the types of bacteria found in shrimp paste in the center of Medan's traditional market. Factors observed included the number of colonies and types of bacteria infected with shrimp paste that emerged from 7 samples of shrimp paste made from this shrimp paste, namely Escherichia coli, Peseudomonas aeroginosa, Proteus vulgaris, Shigella disentryvical, and Salmonella parathypi B/C.